(3NRGfI GdCOH hdH dHGH dSGf GdYQHs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s; (3eMeO Hf GdMSf GdQVj GdCSJQGHGPj , fLe GdOjf,J (B686 (3g` s ((3Ydj Hf eMeO Hf eUWai GdTgjQ HGHf QLH hHGHf GdJQLeGf, GdLRGFQj GdeOfj s)
(3ChdgG (B:s
(3GdcfGjGJ(B: (3CfTO ajgG, hgh GdTGgO GdSGOS hGdKeGfhf HYO GdCQHY efg cCf aYdI de JedC ehGcHgG OjGQ HcQ hde JNdY hde JgH s
(3BNQgG (B:s
(3hJbOeJ JQLeI GdeLfhf aj GdTGgO GdJSYjf hgPG BNQ GdcdGe Ydi TQM GdThGgO GfJgi GdLRA GdKGfj s
(3GdcGajI dGHf GdMGLHs
(3HChdgG Jedc hhba cJHg GdTfbjWj HNWg aj GdeOjfI GdefhQI YGe (B1291(3g``s
(3hHgG fXGe GdJYbjHIs
(3HChdgG agQS ddThGgO s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdfMhs